2014
DOI: 10.1016/s0212-6567(14)70089-7
|View full text |Cite
|
Sign up to set email alerts
|

Teens and dating: study of factors that influence attitudes of violence

Abstract: The results point to the need to integrate the topic of dating violence in adolescent education using active methods with the effective participation of everyone involved in the process (adolescents, parents, teachers and health professionals). Only in this way will it be possible to develop healthy emotional relationship skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
2
6
0
6
Order By: Relevance
“…We found that DV was prevalent among the participants and verbal and psychological violence were the most frequently experienced types of violence in dating relationships, while sexual violence was the least frequently experienced type of violence in dating relationships. These results of the research are consistent with the literature (Barreira et al., ; Boladale, Yetunde, Adesanmi, Olutayo, & Olanrewaju, ; Chan et al., ; Fernandez‐Fuertes & Fuertes, ; Ferreira et al., ; Foshee, Reyes et al., ; Lehrer, Lehrer, & Zhao, ; Ohnishi et al., ; Shorey et al., ; Volpe et al., ; Zhang et al., ). Researchers have identified psychological violence as the most common type of bidirectional violence perpetration in dating relationships (Chan, ; Ferreira et al., ; Ohnishi et al., ; Toplu‐Demirtas et al., ; Volpe et al., ; Zhang et al., ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that DV was prevalent among the participants and verbal and psychological violence were the most frequently experienced types of violence in dating relationships, while sexual violence was the least frequently experienced type of violence in dating relationships. These results of the research are consistent with the literature (Barreira et al., ; Boladale, Yetunde, Adesanmi, Olutayo, & Olanrewaju, ; Chan et al., ; Fernandez‐Fuertes & Fuertes, ; Ferreira et al., ; Foshee, Reyes et al., ; Lehrer, Lehrer, & Zhao, ; Ohnishi et al., ; Shorey et al., ; Volpe et al., ; Zhang et al., ). Researchers have identified psychological violence as the most common type of bidirectional violence perpetration in dating relationships (Chan, ; Ferreira et al., ; Ohnishi et al., ; Toplu‐Demirtas et al., ; Volpe et al., ; Zhang et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…DV is classified as a type of intimate partner violence (IPV) and is defined as physical, sexual, psychological, or emotional violence within dating relationships or between current or former dating partners, which is prevalent from the middle school years throughout young adulthood (Ferreira, Lopes, Aparicio, Cabral, & Duarte, ; Miller, ). DV differs from other types of violence in the way it is experienced and its consequences.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations